Discourses on Social Software - Eijck, Jan van; Verbrugge, Rineke (Texts in Logic and Games, 2009)
Can computer scientists contribute to the solution of societal problems? Can logic help to model social interactions? Are there recipes for making groups with diverging preferences arrive at reasonable decisions? Why is common knowledge important for social interaction? Does the rational pursuit of individual interests put the public interest in danger, and if so, why? Discourses on Social Software sheds light on these and similar questions. This book offers the reader an ideal introduction to the exciting new field of social software. It shows in detail the many ways in which the seemingly abstract sciences of logic and computer science can be put to use to analyse and solve contemporary social problems. The unusual format of a series of discussions among a logician, a computer scientist, a philosopher and some researchers from other disciplines encourages the reader to develop his own point of view. The only requirements for reading this book are a nodding familiarity with logic, a curious mind, and a taste for spicy debate. This title is available in the OAPEN Library - http://www.oapen.org.